Prevalence of Diabetes and Dyslipidemia in Hypertensive Young Adults in a Tertiary Care Centre in Nepal, a Cross Sectional Study - Sharma Lamsal, Kamal; Neupane, Keshab R; Acharya, Niranjan; Lamsal, Dinesh K; Karmacharya, Niraj; Paudel, Deepak; Paudel, Rajan; Sharma, Rabi P (Journal of Institute of Medicine Nepal, 2020)
Introduction Diabetes mellitus (DM) and lipid disorders (LD) in hypertensive patients are associated with increased risk of cardiovascular complications requiring close follow-up and more aggressive treatment. Hence, the present study was done to study the prevalence of diabetes and dyslipidemia in young hypertensive patients i.e.